Leadership Transformation: Job Satisfaction and Organizational Commitment Department of Transportation in Southeast Sulawesi - Syarifuddin, Helmi; Madjid, Rahmad; Daud, Anshar (International Journal of Contemporary Sciences (IJCS), 2024)
This study aims to analytically and descriptively examine the influence of transformational leadership on job satisfaction, organizational commitment, and employee performance. A survey approach was employed, utilizing questionnaire data collection, with a census method due to the relatively small and accessible research population. The data analysis method applied was descriptive analysis. The research findings indicate that transformational leadership in the Transportation Department of Southeast Sulawesi Province is rated sufficiently with an average score of 3.27, indicating that the majority of respondents believe that leaders can influence, motivate, and support employee contributions. Employee job satisfaction is rated as sufficient, with an average score of 3.36, indicating that factors such as challenging work, salary, promotion, and supervision have met employee expectations. Organizational commitment is rated as sufficient with an average score of 3.34, indicating that the majority of respondents have adequate attachment to the organization through affective, continuance, and normative commitment. Additionally, employee performance is rated high, with an average score of 3.59, indicating that respondents perceive good performance in carrying out their duties as Civil Servants in the Transportation Department of Southeast Sulawesi Province.